Polygenic determinants of Parkinson's disease in a Chinese population - Guo, Ji-Feng; Li, Kai; Yu, Ri-Li; Sun, Qi-Yin; Wang, Lei; Yao, Ling-Yan; Hu, Ya-Cen; Lv, Zhan-Yun; Luo, Lin-Zi; Shen, Lu; Jiang, Hong; Yan, Xin-Xiang; et al. (Neurobiology of aging, 2015)
It has been reported that some single-nucleotide polymorphisms (SNPs) are associated with the risk of Parkinson's disease (PD), but whether a combination of these SNPs would have a stronger association with PD than any individual SNP is unknown. Sixteen SNPs located in the 8 genes and/or loci (SNCA, LRRK2, MAPT, GBA, HLA-DR, BST1, PARK16, and PARK17) were analyzed in a Chinese cohort consisting of 1061 well-characterized PD patients and 1066 control subjects from Central South of Mainland China. We found that Rep1, rs356165, and rs11931074 in SNCA gene; G2385R in LRRK2 gene; rs4698412 in BST1 gene; rs1564282 in PARK17; and L444P in GBA gene were associated with PD with adjustment of sex and age (p < 0.05) in the analysis of 16 variants. PD risk increased when Rep1 and rs11931074, G2385R, rs1564282, rs4698412; rs11931074 and G2385R, rs1564282, rs4698412; G2385R and rs1564282, rs4698412; and rs1564282 and rs4698412 were combined for the association analysis. In addition, PD risk increased cumulatively with the increasing number of variants (odds ratio for carrying 3 variants, 3.494). In summary, we confirmed that Rep1, rs356165, and rs11931074 in SNCA gene, G2385R in LRRK2 gene, rs4698412 in BST1 gene, rs1564282 in PARK17, and L444P in GBA gene have an independent and combined significant association with PD. SNPs in these 4 genes have a cumulative effect with PD.